(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is methodical, and it is written on the basis of the results of the research on the characteristics of personality in adolescence. It addresses the role of consciousness in the process of formation and development of the individual, especially in adolescence, as consciousness is raised to a qualitatively new stage in its development. It considers the structure of self-consciousness, and its individual components / self-esteem, the image of «I» /. The development of consciousness in adolescence creates the most favorable conditions for learning activities, which results in gradual clarification and creation of the image of self accomplishments, in forming activity; an individual becomes aware of his place in the world, his abilities and capabilities Practices and procedures are important to identify the three types of relationships: between knowledge and activity levels, educational achievement and the level of activity of students, academic performance and the process of activation of educational activity.